ANALISIS TEMBAGA (Cu) DAN TIMAH (Sn) DALAM JAGUNG (Zea mays L.) KEMASAN KALENG SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Fanny Novelia Ningsih; Zul Afkar; Bahrizal Rizal (Jurnal Periodic Jurusan Kimia UNP, 2013)
Corn (Zea mays L.) is one of the most important food crop in the world. Now a days, there is development in production of canned corn. The media growing corn is possible if using sand and canned, a canned that has possiblity to heavy metal contamination in product of canned corn. This research has purpose to know some kind of solution and volume of best solution in analysis of copper and tin inside canned corn by using atomic absorption spectrofotometry. This research use a wet metode of destruction, the destruction process using the solvent variation: HNO3 p.a, HCl p.a, aquaregia and volume variation : 40, 50, 60 ml. The results of this study showed the highest copper and tin content in the corn canned obtained by using HNO3 p.a 50 ml. The copper contamination use solution HNO3 p.a 50 ml values are 2,4596 mg/kg (Xa), 1,46684 mg/kg (Xb), 1,9882 mg/kg (Y), and 0,9609 mg/kg (Z). The tin contamination use solution HNO3 p.a 50 ml values are 7,5086 mg/kg (Xa), 7,0153 mg/kg (Xb), 6,6779 mg/kg (Y), and 8,1854 mg/kg (Z). The closer to the expary date, the higher values of heavy metal contamination.